Wise and discerning hearts : an introduction to wisdom liturgical theology - Crainshaw, Jill Y., 1962- (Collegeville, Minnesota : The Liturgical Press, 2000)
"A Pueblo book"
Includes bibliographical references (p. 265-280) and index
Keywords: Liturgics -- History